The Rose and The Ring, or The History of Prince Giglio and Prince Bulbo - William Makepeace Thackeray; Dorothy Margaret Stuart (UK The Macmillan Publishing Company Inc., 1930)
A Fire-Side Pantomime for Great and Small Children
M. A. Titmarsh
Between the kingdoms of Paflagonia and Crim Tartary, there lived a mysterious personage, who was known in those countries as the Fairy Blackstick, from the ebony wand or crutch which she carried; on which she rode to the moon sometimes, or upon other excursions of business or pleasure, and with which she performed her wonders. When she was young, and had been first taught the art of conjuring by the necromancer, her father, she was always practicing her skill, whizzing about from one kingdom to another upon her black stick, and conferring her fairy favors upon this Prince or that
Keywords: General